Does labelling differentiate products and create price premiums? The case of tomatoes from northeast Nigeria - Yamauchi, Futoshi; Dauda, Bawa; Balana, Bedru; Edeh, Hyacinth O.; Shi, Weilun (International Food Policy Research Institute, 2024)
This note describes a labelling experiment introduced to crates of tomatoes cool transported from the northeast region of Nigeria to Lagos or Port Harcourt. A label was attached to a random sample of crates to ensure that the quality of tomatoes is orthogonal to the labels and the destination market was not informed of the experiment. The label contained the information on (a) the project (IFPRI), (b) the transportation method (cool transportation), and (c) the origin of tomatoes (Jos or Gombe), as shown below. The experiment was conducted in the first rounds from Jos and Gombe (Lagos), and the fifth round from Jos (Port Harcourt). As expected, the labeled crates were priced higher than the unlabeled crates. About 9 to 33% of the sale price is attributed to improved information on the quality of tomatoes via the labels.